Mangrove Species Diversity as a Coastal Ecosystem Buffer in Sonde Village, Rangsang Pesisir District, Meranti Islands Regency - Pebriandi, Pebriandi; Aprianto, M. Ikhsan; Sribudiani, Evi; Somadona, Sonia; Mardhiansyah, Muhammad; Darlis, Viny Volcherina (Jurnal Biologi Tropis, 2024)
Mangrove diversity in Indonesia, including in Sonde Village, Rangsang Pesisir District, and Meranti Islands Regency, is one of the country's assets that is very important both ecologically, socially, and economically. This study aims to determine the diversity of mangrove species in the Tuah Sonde Forest Farmer Group Community Forest area. The method used was transect with random start with vegetation data collection conducted from June to July 2022. Data analysis includes quantitative descriptive analysis by calculating the Important Value Index (IVI) and the Shannon-Wiener Diversity Index (H'). The results showed that there were six mangrove species found in Sonde Village, namely Rhizophora apiculata, Ceriops tangal, Bruguiera cylindrica, Xylocarpus granatum, Sonneratia alba, and Avicennia marina. Sonneratia alba species dominated at the tree level with the highest INP of 167.66%, while Rhizophora apiculata dominated at the seedling and sapling levels with INPs of 111.52% and 76.74% respectively. The species diversity index (H') at the seedling and sapling level shows a medium category, while at the tree level is in the low category. Mangrove species diversity in Sonde Village is influenced by environmental factors such as tides and human activities, especially illegal logging which has the potential to reduce the sustainability of mangrove ecosystems in the region.